2020
DOI: 10.1186/s42400-020-00047-5
|View full text |Cite
|
Sign up to set email alerts
|

Predicting individuals’ vulnerability to social engineering in social networks

Abstract: The popularity of social networking sites has attracted billions of users to engage and share their information on these networks. The vast amount of circulating data and information expose these networks to several security risks. Social engineering is one of the most common types of threat that may face social network users. Training and increasing users' awareness of such threats is essential for maintaining continuous and safe use of social networking services. Identifying the most vulnerable users in orde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 60 publications
2
26
1
Order By: Relevance
“…Research on behavioral against social engineering attacks has been studied thoroughly by [14], [16]. They proposed a user-centric framework [14] and a prediction approach of an individual's vulnerability [16].…”
Section: B Analysis Concept Of Prevention For Social Engineering Attacksmentioning
confidence: 99%
See 1 more Smart Citation
“…Research on behavioral against social engineering attacks has been studied thoroughly by [14], [16]. They proposed a user-centric framework [14] and a prediction approach of an individual's vulnerability [16].…”
Section: B Analysis Concept Of Prevention For Social Engineering Attacksmentioning
confidence: 99%
“…Social engineering attacks prevention methods are health campaign strategies, health campaign tactics, television advertisements, informational pamphlets, social media [10], ethics of social engineering penetration testing [11], a human as a security sensor framework [12], a personality information processing model [13], characteristic user framework [14], Game-based analysis [15], and predicting individuals' vulnerability [16], computer security policy [17], cyber security practices [18].…”
Section: Introductionmentioning
confidence: 99%
“…Most respondents were also aware of the privacy features of social networking sites, irrespective of gender (11) . Female users are more aware than male users (11) , but they are more susceptible to attacks (12) Table 8 shows the computed multivariate test on the responses of the respondents as to age. As shown on the table under Wilks' Lambda, it revealed that the value is 0.865 with an F-value of 1.298 and a probability value of 0.099 since the p-value is more significant than the 0.05 margin of error; hence, the null hypothesis is accepted.…”
Section: Multivariate Test On the Responses Of The Respondents When Grouped As Tomentioning
confidence: 99%
“…Hence, the null hypothesis is rejected, resulting in a significant relationship on social networking security awareness when grouped according to educational attainment. According to Albladi & Weir, the educational level has no substantial effect on users' vulnerability, as shown by the regression study of the susceptibility to attacks (12) . Table 10 the computed multivariate test on the respondents' responses to using social media.…”
Section: Multivariate Test On the Responses Of The Respondents When Grouped As Tomentioning
confidence: 99%
“…In the last decades, users have interacted with many platforms on the Internet, which lead to them being attacked by hackers using social engineering attacks [13] and their data being shared on the Internet [14]. Some studies indicate that social engineering relies on human nature and vulnerabilities to hack into organizational systems.…”
mentioning
confidence: 99%